PENGARUH LITERASI KEUANGAN DAN PERILAKU KEUANGAN ANGGOTA TERHADAP PENDAPATAN KOPERASI MITRA DHUAFA CABANG KEDUNGBANTENG KABUPATEN TEGAL - Asep Saeful Alam; Dwi Harini; Yenny Ernitawati (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
The importance of financial literacy and good financial behavior in improving the economic well-being of cooperative members is paramount. The lack of educational and training programs focused on enhancing financial literacy and behavior within cooperatives potentially limits the income growth of members. Cooperatives, as microfinance institutions, are expected to significantly contribute to increasing their members' income through better financial education and management. This study aims to analyze the influence of financial literacy and financial behavior on the income of members of the Mitra Dhuafa Cooperative, Kedungbanteng Branch, Tegal Regency. The research method used is a quantitative approach with a survey method. The population of this study includes all members of the Mitra Dhuafa Cooperative, Kedungbanteng Branch, Tegal Regency. The sample of the study consisted of 98 respondents selected through random sampling. Data collection was conducted using questionnaires that have been tested for validity and reliability. The results showed that financial literacy (X1) partially has a significant effect on income. This is indicated by a t-value of 7.538, which is greater than the t-tabel value (1.661) with a significance of 0.000 < 0.05. Members' financial behavior (X2) also partially has a significant effect on income, with a t-value of 2.456, which is greater than the t-tabel value (1.661) at a 5% significance level. Simultaneously, financial literacy and members' financial behavior significantly affect the cooperative's income. This is shown by an F-value of 394.195, which is greater than the F-tabel value (3.938) with a significance of 0.000 < 0.05.